EVALUASI MUTU BETON PADA PROYEK PEMBANGUNAN GEDUNG PARKIR RUMAH SAKIT TELOGOREJO SEMARANG Di PT. Adhi Karya (Persero) Tbk â Semarang - , IRWAN KURNIAWAN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Concrete is the main component of a building structure. Therefore, the concrete must be completely taken into account quality and quality in order to minimize the risk of failure of the structure. Thus it is necessary to evaluate the quality in any concrete work. Evaluation of the quality of the concrete is intended to determine whether the quality of the concrete on the project has been planned to meet the quality of the Work Plan and the terms and structures to ensure the burden prisoners still within a safe limit. The method used is the slump test and manufacture of cylindrical specimen diameter 15 cm and height of 30 cm on each casting. Then tested using engine compression test and evaluation based on provisions of SNI 03-2847-2002. The results of the evaluation none of the test object does not meet the specified requirements. All the compressive strength of concrete specimen quality K-350 no less than 307.83 kg/cmÂ² and all the compressive strength of concrete specimen quality K-400 no less than 357.83 kg/cmÂ². These results showed that the quality of the concrete in the parking deck for Development of Semarang Telogorejo hospital has met the standard of quality of concrete that had been planned in work Plan and the terms.